Effect of the heat-induced whey proteins/κ-casein complex on the acid gelation of yak milk. Issue 12 (11th February 2015) - Xu, Weiyi; He, Shenghua; Ma, Ying; Zhang, Yixin; Wang, Rongchun
<x xml:space="preserve">Abstract</x> The soluble whey protein/κ-casein complexes were predominant in changing the rheological properties of yak milk yoghurt.